1999
DOI: 10.1093/jnci/91.19.1647
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance and the Lung Resistance-Related Protein in Human Colon Carcinoma SW-620 Cells

Abstract: LRP is involved in resistance to doxorubicin, vincristine, etoposide, paclitaxel, and gramicidin D and has an important role in the transport of doxorubicin from the nucleus to the cytoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
150
1
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 19 publications
8
150
1
2
Order By: Relevance
“…19 This hypothesis has been corroborated by recent data regarding an MVP-dependent MDR phenotype induced by differentiation-inducing agents in colon cancer cells that was based on nuclear drug extrusion. 20 However, only a very few studies were able to localize considerable amounts of MVP at the nuclear membrane or in the nucleus. In most cell types, MVP was described to be localized in the cytoplasm or the perinuclear region.…”
Section: Discussionmentioning
confidence: 99%
“…19 This hypothesis has been corroborated by recent data regarding an MVP-dependent MDR phenotype induced by differentiation-inducing agents in colon cancer cells that was based on nuclear drug extrusion. 20 However, only a very few studies were able to localize considerable amounts of MVP at the nuclear membrane or in the nucleus. In most cell types, MVP was described to be localized in the cytoplasm or the perinuclear region.…”
Section: Discussionmentioning
confidence: 99%
“…41 It was argued that these conflicting results might be due to patient population. 41 Akiyama et al showed that the induction of LRP by sodium-butyrate and the experiments using the ribozyme against LRP in KB 3-1 cells did not show the relationship between cisplatin-cytotoxicity and LRP, 48 although the direct evidence that LRP could transport cisplatin outside nucleus, is not still clear. Although our study showed no relation between LRP gene expression and clinical response to cisplatin-based chemotherapy, further examination will be required to conclude any relationship between cisplatin-cytotoxicity and LRP in vitro or in clinic.…”
Section: Mrp1 Mrp2mentioning
confidence: 99%
“…Their considerable abundance and striking evolutionary conservation argue for their important role in cell survival (4). Several lines of evidence have suggested that vaults may play an important role in intracellular detoxification processes, and thus may function in the multidrug resistance (MDR) of cancer cells (5).…”
Section: Introductionmentioning
confidence: 99%